The cross-cultural adaptation of the DASH questionnaire in Thai (DASH-TH) - Siam Tongprasert (2018)
Study design Clinical measurement. Introduction Currently there are no self-report questionnaires in Thai to evaluate disability levels in patients suffering from upper extremity musculoskeletal disorders. Purpose of the study To translate and cross-cultural adaptation the disabilities of the arm, shoulder and hand (DASH) questionnaire to Thai version and to evaluate content validity, construct validity and internal consistency of the questionnaire. Methods The DASH-TH was produced by following cross-cultural adaptation guidelines stated by the Institute for Work and Health (IWH). Forty Thai patients with arm, shoulder or hand problems participated in field testing of the questionnaire. Content validity was determined by obtaining the item-objective congruence (IOC) value for each questionnaire item. Correlation between the DASH-TH score and numeric rating scale was used to assess construct validity. Internal consistency of DASH-TH was measured using Cronbach's alpha coefficient. Results Forty patients (14 males, 26 females) with arm, shoulder or hand problems enrolled in the present study. The average age of patients was 44.8 years. The index of item-objective congruence (IOC) of each item ranged from 0.7 to 1.0. The Cronbach's alpha coefficient of the questionnaire was 0.938. There was no correlation between DASH-TH score and numeric rating scale. Conclusion The DASH-TH has high content validity and internal consistency. Level of evidence N/A.7 © 2014 Hanley and Belfus, an imprint of Elsevier Inc. All rights reserved.